Polymorphisms in the vitamin D system and mortality - The Tromsø study - Jorde, Rolf; Wilsgaard, Tom; Grimnes, Guri (The Journal of Steroid Biochemistry and Molecular Biology, 2019)
Vitamin D deficiency is associated with diabetes, cancer, immunological and cardiovascular diseases as well as increased mortality. It has, however, been difficult to show a causal relation in randomized, controlled trials. Mendelian randomization studies provide another option for testing causality, and results indicate relations between the serum 25-hydroxyvitamin D (25(OH)D) level and some diseases, including mortality. We have from the Tromsø Study in 2012 published non-significant relations been vitamin D related single nucleotide polymorphisms (SNPs) and mortality, but have since then genotyped additional subjects, the observation time is longer and new SNPs have been included. For the present study genotyping was performed for SNPs in the NADSYN1, CYP2R1, GC and CYP24A1, VDR, CUBILIN and MEGALIN genes in 11 897 subjects who participated in the fourth survey of the Tromsø Study in 1994–1995. Serum 25(OH)D levels were measured in 6733 of these subjects. Genetic scores based on SNPs related to the serum 25(OH)D level ( NADSYN1 and CYP2R1 SNPs (synthesis score) and GC and CYP24A1 SNPs (metabolism score)) and serum 25(OH)D percentile groups were created. Mortality data was updated till end of March 2017 and survival analysed with Cox regression adjusted for sex and age. During the observation period 5491 subjects died. The 25(OH)D synthesis (but not the metabolism) genetic score and the serum 25(OH)D percentile groups were (without Bonferroni correction) significantly related to mortality in favour of high serum 25(OH)D. None of the SNPs in the VDR or MEGALIN genes were related to mortality. However, for the rs12766939 in the CUBILIN gene with the major homozygote as reference, the hazard ratio for mortality for the minor homozygote genotype was 1.17 (1.06–1.29), P < 0.002. This should be viewed with caution, as rs12766939 was not in Hardy-Weinberg equilibrium. In conclusion, our study confirms a probable causal but weak relation between serum 25(OH)D level and mortality. The relation between rs12766939 and ...